Conformational landscapes of rigid and flexible molecules explored with variable temperature ion mobility-mass spectrometry - Xudong Wang; Emma Norgate; Junxiao Dai; Florian Benoit; Tony Bristow; Richard M. England; Jason M. D. Kalapothakis; Perdita E. Barran (Nature Communications)
Abstract Understanding the effect of temperature to the structural integrity of proteins is relevant to diverse areas such as biotechnology and climate change. Variable temperature ion mobility-mass spectrometry (VT-IM-MS) can measure the effect of temperature on conformational landscapes. To delineate collision effects from structural change we report measurements using molecules with different degrees of rigidity namely: poly (L-lysine) (PLL) dendrimer, ubiquitin, β-casein and α-synuclein from 190-350 K. The CCS of PLL dendrimer varies with temperature consistent with collision theory, by contrast, the structure of each protein alters with notable restructuring at 350 K and 250 K, following predicted in vitro stability curves. At 210 K and 190 K we kinetically trap unfolding intermediates. For alpha-synuclein, the 13+ ions present two distinct conformers and VT-IM-MS measurements allow us to calculate the transition rate and activation energies of their conversion. These data exemplify the capacity of VT-IM-MS to provide insights on the thermodynamics of conformational restructuring.